Crystal Structures of Z and E ortho‐Tetrafluoroazobenzene. Issue 35 (19th December 2017) - Hermann, Daniela; Schwartz, Heidi A.; Ruschewitz, Uwe
Abstract: The crystal structures of Z ‐ ( Pna 21, Z =4; single‐crystal X‐ray diffraction data) and E ‐ ortho ‐tetrafluoroazobenzene ( Pna 21, Z =4; synchrotron powder diffraction data) were solved and refined. These structural analyses reveal that the phenyl rings are almost coplanar in the E isomer, whereas a tilting by 67.8(5)° was found in the Z isomer. This leads to significantly different molecular shapes (longest elongations 13.2 Å x 8.1 Å x 4.0 Å for the E isomer vs. 9.6 Å x 7.0 Å x 6.9 Å for the Z isomer). A comparison of the supramolecular structures of Z ‐ and E ‐ ortho ‐tetrafluoroazobenzene with other known fluorinated azobenzenes shows that mainly H … F interactions occur in both isomers of ortho ‐tetrafluoroazobenzene, whereas H … F and F … F interactions exist in E ‐4H, 4H'‐octafluoroazobenzene, only F … F interactions in E ‐perfluoroazobenzene, and N … C, F … C as well as F … F interactions in Z ‐perfluoroazobenzene. Abstract : The crystal structures of Z ‐ ( Pna 21, Z =4) and E ‐ ortho ‐tetrafluoroazobenzene ( Pna 21, Z =4) were solved and refined from X‐ray single crystal and synchrotron powder diffraction data, respectively. A detailed analysis of the molecular and supramolecular structure reveals distinct differences in comparison to parent azobenzene as well as other fluorinated derivatives.